Perancangan dan Aplikasi Alat Sistem Irigasi Otomatis pada Budidaya Paprika di Desa Candikuning (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2017)
Service activities that conducted on horticultura farmer group in the Candikuning village moreemphasis on irrigation water use efficiency in irrigation system pilot project in the cultivation ofbell peppers through automation techniques. Through this activity is expected to be availablehuman resources who can operate and develop automation equipment provision of irrigationwater to the agricultural sector, especially the cultivation of peppers. To achieve the output targetshas been made of demonstration plots with application of irrigation water supply automation toolbased operating system Mikrontroler Atmega 16. For availability of human resources capable ofrunning, maintaining, and even develop such equipment has also been conducted socializationactivities through the direct delivery of the device to the operating system some members offarmers as partners devotion
Keywords: bell peper; irrigation; automation